Assessment of diversity and distribution of benthic communities in Hopavågen Bay, Sletvik area (Norway) (Geo-Eco-Marina, 2017)
The study presents the results of macrovisual characterisation of diversity and distributional pattern of benthic assemblages of fauna and flora, influenced by the hydrodynamic and geomorphological conditions in the Hopavågen Bay. The surveys were carried out by underwater visual census in May 2012 and August 2013, as part of the eco-hydraulic work package (PISCES) of the HYDRALAB IV project. It studied the interactions of vegetation with hydrodynamics, focusing on the ability of physical models of plants to mimic real vegetation, in order to enhance the production of more realistic surrogates. In average, 30 species of macroinvertebrates and 15 species of macrophytes have been identified. The seasonal distribution of biotic components is also presented.
Keywords: Norway Sea; landlocked bay; biodiversity; benthos; underwater visual census; seasonal distribution